2017
DOI: 10.1007/s13187-017-1311-7
|View full text |Cite
|
Sign up to set email alerts
|

Team-Based Learning Module for Undergraduate Medical Education: a Module Focused on the Human Papilloma Virus to Increase Willingness to Vaccinate

Abstract: Human papilloma virus (HPV) vaccination rates lag behind other vaccines, primarily because of weak provider recommendations, and are associated with nearly 30,000 new cancer diagnoses a year. Educating medical students about HPV using active, team-centered learning may increase assimilation of information and may increase vaccination rates. A team-based learning (TBL) module focused on HPV for first-year medical students about HPV will better increase knowledge and likeliness to vaccinate than traditional educ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 8 publications
0
24
0
Order By: Relevance
“…Lack of HPV knowledge in addition to unawareness about the link of HPV with oral/oropharyngeal cancer was seen in recent survey studies with suggested interventional measures including interactive workshops for preclinical students and team-based learning. 20,21,34,35 A recent study that surveyed medical and non-medical students from Ukraine showed a poor level of knowledge regarding HPV-related oral and rectal cancers among all groups of students. 36 Another recent study that surveyed female college students from China, reported similar defect in knowledge about the ability of HPV to cause oral cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lack of HPV knowledge in addition to unawareness about the link of HPV with oral/oropharyngeal cancer was seen in recent survey studies with suggested interventional measures including interactive workshops for preclinical students and team-based learning. 20,21,34,35 A recent study that surveyed medical and non-medical students from Ukraine showed a poor level of knowledge regarding HPV-related oral and rectal cancers among all groups of students. 36 Another recent study that surveyed female college students from China, reported similar defect in knowledge about the ability of HPV to cause oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…For example, less than a quarter of the clinical students knew about HPV association with oropharyngeal cancer, and less than one‐fifth were aware of HPV association with penile cancer. Lack of HPV knowledge in addition to unawareness about the link of HPV with oral/oropharyngeal cancer was seen in recent survey studies with suggested interventional measures including interactive workshops for preclinical students and team‐based learning 20,21,34,35 . A recent study that surveyed medical and non‐medical students from Ukraine showed a poor level of knowledge regarding HPV‐related oral and rectal cancers among all groups of students 36 .…”
Section: Discussionmentioning
confidence: 99%
“…This challenges organizations to explore alternative methods to offer education on communication strategies to diverse healthcare providers moving forward. Recent innovative educational approaches such as team-based learning where medical students are taught and evaluated in small groups on their HPV knowledge and communication is just one example [74] .…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Increases in intention to recommend the HPV vaccine have been achieved with a previous intervention, but consisted of an intensive week-long exercise. 21 Our intervention is more practical as it consisted only of a single lecture given to medical students by an expert, which most stated was their preferred source of information.…”
Section: Discussionmentioning
confidence: 99%